Оптимальний розподіл реактивної потужності між синхронними і асинхронізованими турбогенераторами - Сегеда, М.С.; Олексин, В.П.; Олексин, А.В. (Технічна електродинаміка, 2012)
Based on the Lagrange multiplier method, methodology, mathematical and digital models of optimal var dispatch between synchronous and asynchronized (synchronous operation) turbo generators at TPS were developed; these take into account the influence of generator transformers and auxiliary service transformers, as well as secure the active power minimum losses. It was determined that generators reactive power optimum values depend on their types, their active load, generator transformers and auxiliary service transformers parameters, and the unit auxiliaries power circuit.